Research and Development of Mobile Marine Satellite Antenna System in Vietnam - Anh Tam, Ho; Thi Huong Giang, Do; Muoi, Dang Van; Dinh Van, Nguyen; Viet Hung, Nguyen; Huu Duc, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 2, 2019)
Abstract: A second version of the mobile marine satellite communication signal receiver station has been designed, manufactured, assembled and tested using domestically engineered mechanical modules, commercial and low-cost integrated sensors, motors and drivers. The operating mechanical components have been developed in the form of independently operating modules with handling ease and high sensitivity at a “clearance” in the order of 10µm. The sensors are of high and firm integration and good noise compensation facilities. The appropriately developed automatic control algorithms and software allow efficient and safe searching and following the broadcasting satellite of the antenna device installed on a marine transport boat. Compared to the previous version, this new development has more optimal dimensions, is easier and more flexible to start up and operate with operating parameters of pitch: 15-80° (±0.5°), yaw: of 0-360° (±0.25°), and polarization angle of 0-360° (±0.5°). The antenna turn rates are of ~12°/s and 12°/s 2 . All the components of the complete system are water- and weather proof and packaged to ensure safe operation in marine conditions. Running tests have been successfully taken in real sunny weather conditions on a sea boat speeding at 30 km/h with a wind velocity up to 19 km/h. The article concludes that domestically engineered, the device is more financially efficient than imported counterpart equipments as well as promising in terms of technology transfer to mass production by domestic businesses. Keywords: Satellite receiver antenna, marine satellite antenna, antenna angle controller, sensors. References [1] B. Schneiderman, Executive Roundtable on Maritime and Energy Markets, Satellite Executive Briefing 11 (8) (2018) 9. [2] L.M. Bradbury, D. Diaconu, S. Molgat Laurin, A.M. Beattie, C. Ma, I.S. Spydevold, H.C. Haugli, R.E. Zee, J. Harr, F. Udnæs, NorSat-2: Enabling advanced maritime communication with VDES, Acta Astronautica 156 (2019) 44-50. [3] Y.J. Song, P.S. Kim, D.G. Oh, et al., Development of mobile broadband interactive satellite access system for Ku/Ka band, International journal of satellite communications and networking 24 (2007) 101-117. [4] Y.J. Song, M.S. Shin, B.H. Kim, et al, Development of mobile broadband satellite access system for Ka/Ku-band satellite communications, Ieice transactions on communications, e87b (2004) 2152-2161. [5] S. Pekowsky, G Pousset, Y. Levy, MobileTV Receiver Technology with special emphasis on DVB-SH, international journal of satellite communications and networking 27 (2009) 275-293. [6] http://www.raysat.com/mobile_satellite_television_antennas. [7] Nguyễn Hữu Đức, Bùi Đình Tú, Nguyễn Thị Ngọc, Đồng Quốc Việt, Đỗ Thị Hương Giang, Trạm thu di động thông tin vệ tinh dựa trên sensơ từ trường độ nhạy cao ứng dụng trên tàu biển, Tuyển tập Hội thảo khoa học Công nghệ vũ trụ và ứng dụng, Hà Nội, 2014. [8] M. Geissler, F. Woetzel, M.Böttcher, S. Korthoff, A.Lauer, M.Eube, R. Gieron, Roman, Innovative phased array antenna for maritime satellite communications, EuCAP 2009. 3rd European Conference on Antennas and Propagation 2009, pp.735-739. [9] http://www.orbit-cs.com/modular-maritime-communications-system [10] https://www.digisat.org/maritime-satcom-vsat [11] https://paracomm.co.uk/ [12] https://www.intelliantech.com/?lang=en. [13] Nguyễn Hữu Đức, Báo cáo tổng kết đề tài đề tài “Thiết kế và chế tạo trạm thu di động thông tin vệ tinh dựa trên sensơ từ trường độ nhạy cao ứng dụng trên tàu biển”, Chương trình KH&CN quốc gia về Công nghệ vũ trụ giai đoạn 2013-2015, Hà Nội, 2016.